Shifting Home Energy Consumption Through a Holistic Understanding of the Home System of Practice - Eon, Christine; Breadsell, Jessica; Morrison, Gregory; Byrne, Joshua (Palgrave Macmillan, 2019)
This chapter describes the concept of the home system of practice, which can be used to provide a deeper understanding of the social system of the home and inform long-term solutions for enabling domestic energy reduction. More traditional methods have attempted to persuade occupants to change behaviour through the use of information campaigns and feedback technology. However, these interventions are usually short lived as they ignore the underlying reasons for practices to occur. A more effective solution is through practice-oriented design, which co-creates innovative technology with the user. In addition, the emergence and use of automated technology enables practices to act independently of the user. Yet, the success of automation is also reliant on an understanding of the home system of practice, occupant needs and skills.